School Meals Program and Its Impact Towards Student’s Cognitive Achievement - Rahma Nida; Dwi Darma Puspita Sari (Journal of Economics Research and Social Sciences, 2023)
Nutrition food is one of the factors influencing student academic development. By providing a good nutrition for children in school is one of the way to increase economy development in Indonesia. School meals program has important role in order to improve children participation and children performance in school. Some previous research founds that nutrition food ables to increase children cognitive. However, those have not taken into account the direct impact of school meals program on children cognitive. Therefore, this study aims to analyze the direct impact of school meals program toward children cognitive. The data was taken from Indonesia Family Life Survei (IFLS) wave 5. This study is conducting Propensity Score Matching method to knowing the impact of school meal program on children cognitive. The result shows that school meal program has impact to increase children cognitive score on mathematic. It shows that these program has impact on children score by 0.2 point higher than children in school without school meal program.